Transformasi Dakwah dalam Meningkatkan Efektivitas Penanganan Stunting di Kabupaten Langkat - Amril, Amril; Kholil, Syukur (Jurnal Studi Ilmu Sosial dan Politik, 2024)
Purpose: This study aimed to explore how religious dakwah can raise community awareness and participation in stunting prevention efforts in Langkat Regency, where the prevalence of stunting is higher than the national average. This study introduced a novel approach by integrating religious dakwah with health communication to address stunting in rural areas. Methodology: A qualitative case study approach was used in the Langkat Regency, Indonesia. Newcomb’s Symmetrical Communication Theory was applied to create balanced two-way communication among religious leaders, healthcare workers, and the community. Data were collected through in-depth interviews with religious leaders, healthcare workers, and mothers of young children to capture their experiences and perspectives. Results: The findings demonstrated that combining transformative dakwah with health education effectively bridges communication gaps, increases community involvement, and enhances awareness of child nutrition. This integrated approach was found to be particularly effective in encouraging preventive behaviors within the community. Limitations: This study is limited to the specific cultural and geographical context of the Langkat Regency, which may affect the generalizability of the results to other regions with different cultural settings. Contribution: This study contributes to the field of health communication and community health by demonstrating the potential of integrating religious dakwah with health programs to prevent stunting. It is especially valuable for stakeholders in the health and religious sectors to seek culturally sensitive approaches to public health issues.